2017
DOI: 10.3389/fnins.2017.00219
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Sedentary Behavior: Effects on Academic Performance, Meta-Cognition, and Sleep

Abstract: There is growing interest in using activity workstations as a method of increasing light physical activity in normally sedentary environments. The current study (N = 117) compared the effects of studying in college students while slowly pedaling a stationary bike with a desktop with studying at traditional desks across 10 weeks in an academic semester. The students were assigned to study either on the stationary bike or at a traditional desk located in the campus library for a minimum of 2 h a week. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
(49 reference statements)
4
21
0
2
Order By: Relevance
“…Further, treatment, heart rate, and their interaction were found to be significant across time points. This result is similar to prior studies with adolescents, indicating that when given the opportunity to exercise, students will do so (Deforche, Van Dyck, Verloigne, & De Bourdeaudhuij, 2010;Fedewa, Abel, & Erwin, 2017;Pilcher, Morris, Bryant, Merritt, & Feigl, 2017).…”
Section: Resultssupporting
confidence: 88%
“…Further, treatment, heart rate, and their interaction were found to be significant across time points. This result is similar to prior studies with adolescents, indicating that when given the opportunity to exercise, students will do so (Deforche, Van Dyck, Verloigne, & De Bourdeaudhuij, 2010;Fedewa, Abel, & Erwin, 2017;Pilcher, Morris, Bryant, Merritt, & Feigl, 2017).…”
Section: Resultssupporting
confidence: 88%
“…The lack of decreased performance in areas such as cognitive control, attention, and typing between seated conditions and an active workstation in the current study supports a consideration of active workstation implementation for not only the workplace but environments that would benefit from breaks in sedentary behavior, including classrooms [50]. Given the documented health benefits of walking or cycling during work, the absence of considerable detriments to cognitive performance would seem to suggest that the use of alternative workstations is beneficial to traditionally sedentary environments [51].…”
Section: Discussionsupporting
confidence: 60%
“…Benefits of exercise while performing work tasks or schoolwork are evident in the literature. Bryant et al (2015) and Pilcher et al (2017) published about research performed at Clemson University in which they studied the effects of light activity (the use of Bike Desks) on academic performance and sleep quality. While Soyeur, Unalan, and Elmali (2010) reported that fatigue is related to impaired academic performance (as cited in Nagane, 2004), Bryant et al found that those who rode the bikes while performing schoolwork maintained better sleep quality, which correlated positively with academic performance.…”
Section: Effects Of Physical Activity On Academic Performancementioning
confidence: 99%
“…Light activity on Bike Desks can help with this as bicycling can burn 100-200 calories per hour (Villablanca, 2015, p. 514). Pilcher et al (2017) reported that in addition to addressing obesity and heart disease, research has shown that light or moderate activity may decrease anxiety (as cited in Fox, 1999) and lead to an improved quality of life (as cited in Oka et al, 2000). The Kresge Library purchased two bikes "as an alternative, health-oriented work station, in keeping with the wellness goals of Oakland University" (Pedal, 2016).…”
Section: Bike Desks In Librariesmentioning
confidence: 99%
See 1 more Smart Citation